Tolerizing Strategies for the Treatment of Autoimmune Diseases: From ex vivo to in vivo Strategies - Cauwels, Anje; Tavernier, Jan (Frontiers in Immunology, 2020)
Autoimmune diseases such as multiple sclerosis (MS), type I diabetes (T1D), inflammatory bowel diseases (IBD) and rheumatoid arthritis (RA) are chronic, incurable, incapacitating and at times even lethal conditions. Worldwide, millions of people are affected, predominantly women, and their number is steadily increasing. Currently, autoimmune patients require lifelong immunosuppressive therapy, often accompanied by severe side effects and adverse risks. Targeting the fundamental cause of autoimmunity, which is the loss of tolerance to self- or innocuous antigens, may be achieved via various mechanisms. Recently, tolerance-inducing cellular therapies, such as tolerogenic dendritic cells (tolDC) and regulatory T cells (Treg) have gained considerable interest. Their safety has already been evaluated in patients with MS, arthritis, T1D and Crohn’s disease, and clinical trials are underway to confirm safety and therapeutic potential. Cell-based therapies inevitably are expensive and time-consuming, requiring laborious ex vivo manufacturing. Therefore, direct in vivo targeting of tolerogenic cell types offers an attractive alternative and several strategies are being explored. Type I IFN was the first disease-modifying therapy approved for MS patients, and approaches to endogenously induce IFN in autoimmune diseases are being vigorously pursued. We here review and discuss tolerogenic cellular therapies and targeted in vivo tolerance approaches and propose a novel strategy for cell-specific delivery of type I IFN signaling to a cell type of choice.